Beauty and the beast and other tales of enchantment - Chambless, Jane (New York : Golden Book ; Racine, Wis. : Western Pub. Co., 1986)
Three fairy tales include "Beauty and the Beast," "The Frog Prince," and "The Six Swans."
4.7
3-6
Keywords: Fairy tales; Fairy tales; Folklore -- Germany; Fairy tales